Efeito da fadiga mental no desempenho durante um jogo de voleibol de praia - Gomes, Jarbas Rállison Domingos (2019)
Mental fatigue refers to a psychological change, prolongs the duration of the demanding cognitive activities, cause of episodes of lack of energy and fatigue. However, it is not clear if a mental fatigue can influence your performance during a beach volleyball game. The aim of the study was to analyze the effects of mental fatigue during the beach volleyball game. This is an experimental study with a crossover design. The athletes were young in the stands (16,1 ± 0,9 years, 74,5 ± 8,8 kg, 183,1 ± 2,8 cm, 12,6 ± 4,5 kg of fat, 41,4 ± 15,9 kg of lean mass with 2,7 ± 0,6 years of experience in national and international competitions. The athletes performed beach volleyball matches according to the rules of the International Volleyball Federation in two different conditions, with a period of 48. The experimental condition (EX) was used in a game after 30 minutes of cognitive activity required through the Stroop Task. The control condition (CT) consisted of 30 minutes without demanding physical activity. Were subjected to mental motivation exercises and motivation during the Stroop Task. The exercise was measured during four perspectives: physical performance, technical-tactical performance, decision making and skill execution of the attack. The physical performance was analyzed through the perception subjective of effort (RPE), the heart rate (HR), the amount of jump and the amount of hits during the game, as well as the vertical jump after the game. For an evaluation of technical performance, the coefficient of performance and fundamentals were used: serve, reception, set, attack, block and defense. Decision making and the ability to execute the exercise were through the Instrument for the Evaluation of the Performance of the Game (GPAI). The sensation of mental fatigue had a major impact on Stroop's task (p= 0,0001) and was significantly greater in previous experience. The value of the one-way ANOVA of the mind proved a significant amount of errors (p= 0,01) at E20 to E30. An analysis of the PSE showed that the differences between the living conditions (p= 0,002) and between the moments (p= 0,0001) being greather in EX condition. HR that appears in relation to the moments (p= 0,0001) in two conditions. The amount of jump and hits during the beach volleyball game, which is not the same, are the differences between the conditions EX an CT (p<0,05). The comparative analysis of the technical performance, the CT condition presented a better attack when compared to the EX condition (p<0.05) through the coefficient of performance and efficacy. The CT condition presented a higher decision-making index when compared to the EX condition. There was no significant difference in the skill execution index between the conditions (p <0.05). Mental fatigue impairs performance during a beach volleyball game.